The Influence of Islamic Financial Literacy on the Decision to Save in Islamic Banks among Gen Z Students at UTM - Noval Bahari Ardiansyah; Achmad Budi Susetyo (Al-Iffah: Journal of Islamic Sciences Research, 2025)
This study aims to analyze the effect of Islamic financial literacy on saving decisions at Islamic banks for Generation Z students at Trunojoyo Madura University (UTM). Islamic financial literacy is an important aspect in supporting financial behavior in accordance with Islamic principles, especially among the younger generation. This research uses a quantitative approach with a survey method through distributing questionnaires to active UTM students who fall into the Generation Z category. The data obtained were analyzed using simple linear regression to determine how much influence Islamic financial literacy has on saving decisions. The results showed that Islamic financial literacy has a positive and significant effect on saving decisions at Islamic banks. This finding indicates that the higher the students' understanding of the concept of Islamic finance, the more likely they are to choose Islamic banks as a place to save. Therefore, increasing Islamic financial literacy needs to be a concern in order to support the development of the Islamic banking industry in Indonesia.